Emerging Digital Trends in Virology Software: Optimizing Viral Discovery, Surveillance,and Patient Management. - Mohd. Wasiullah; Piyush Yadav; Aman Kumar Maurya (International Journal of Virus Studies, 2026)
Virology and antiviral therapeutics are being reshaped by rapid advances in computational tools, automation platforms, and virus-focused digital health applications. Software systems now span the entire virology value chain, from in silico viral target identification and antigen design, to AI-supported clinical trial management for vaccines and antivirals, to post-marketing pharmacovigilance and patient-facing mobile tools. This review examines current and emerging software trends relevant to virus studies, emphasizing applications in viral discovery, molecular modeling, high-throughput screening, real-world evidence (RWE) for viral diseases, and digital support for infected or at-risk populations. Particular attention is given to artificial intelligence (AI), machine learning (ML), cloud computing, and integrated virology data ecosystems that enable faster response to outbreaks, improved vaccine and antiviral development, and more precise patient monitoring. The article concludes with a discussion of future opportunities and challenges around interoperability, ethical AI, cybersecurity, and human-AI collaboration within virus research and viral disease management.
Keywords: Antiviral Drug Discovery; Machine Learning; Pharma 4.0; Real-world evidence; Vaccine informatics; Viral genomics; Virology software; artificial intelligence; digital health; viral surveillance